Electronics remote lab integration into a MOOC – Achieving practical competences into MOOCs - Loro, Felix Garcia (2017)
Massive Open Online Courses (MOOCs) phenomenon introduces a new philosophy in educational models. Regardless of users’/students’ motivation when enrolling (lifelong learning, educational support, interest in new educational areas, etc.), MOOCs expand the ways of reaching knowledge. Flexibility is one of the key aspects of this new educational methodology. This flexibility has to be expanded/translated to all the aspects/features of the course. For educational institutions, traditional approaches must be left behind when designing courses and must provide a new approach to educational process. MOOCs fit very well to several areas of knowledge. However, they involve significant challenges for science MOOCs to be really effective, especially in developing courses. These educational challenges are highlighted in courses which need to offer practice-oriented learning in order to build successful crosscurricular capabilities and abilities. Nowadays, educational institutions trust in experimentation as one of the pillars in which learning is based. In fact, theoretical models used in books and in traditional classrooms just try to bring closer to students the actual behavior of real systems. Unfortunately, it is not possible to provide students with a laboratory in a totally/one hundred percent remote learning environment. This paper deals with the results of the integration of a remote laboratory in a MOOC; how it has been taken advantage of VISIR pros and how its cons have been solved, as well as the evolution of the global system (LMS+VISIR) in continuous improvement.